Pemanfaatan Quizizz Sebagai Media Pembelajaran Interaktif - Santy Handayani; Didik Nur Huda; Siwi Puji Astuti (Institut Teknologi dan Bisnis Semarang, 2023)
The purpose of our community service activities is to introduce and socialize the creation and use of Quizizz-based learning media for Trisoko Middle School teachers. The target of this community service activity is the Trisoko Middle School teachers. The method used is the method of training and mentoring as well as discussion. The training is carried out by introducing and socializing the creation and use of Quizizz-based learning media, the material provided during the training includes steps to create and use Quizizz-based learning media. The material was delivered using the Zoom application, due to the Covid 19 endemic conditions that did not allow face-to-face meetings. The output of community service activities to residents is the skills of Trisoko's teachers in planning and creating Quizizz-based learning media.